A Cytokinin Analog Thidiazuron Suppresses Shoot Growth in Potted Rose Plants via the Gibberellic Acid Pathway - Çelikel, Fisun G.; Zhang, Qingchun; Zhang, Yanlong; Reid, Michael S.; Jiang, Cai-Zhong (Frontiers in Plant Science, 2021)
Application of thidiazuron (N-phenyl-N’-1, 2, 3-thiadiazol-5-ylurea, TDZ), a non-metabolized cytokinin analog, to inhibit the leaf yellowing that occurs after pinching potted rose plants, resulted in compact plants with shorter shoots and thicker internodes. Two weeks after treatment with 100 μM TDZ, new shoots were half as long as those in control plants, and stem diameters were about 40% greater. This effect of TDZ is associated with changes in cell architecture. Although TDZ treatment stimulated ethylene production by the plants, inhibitors of ethylene biosynthesis (2-aminoethoxyvinyl glycine - AVG) or action (silver thiosulfate - STS) did not affect the plants’ response to TDZ. We found that TDZ treatment significantly suppressed expression of bioactive GA biosynthesis genes encoding GA3 and GA20 oxidases and slightly increased expression of GA catabolism genes encoding GA2 oxidase. Application of gibberellic acid (GA3) and TDZ together resulted in normal elongation growth, although stem diameters were still somewhat thicker. Our results suggest that TDZ regulates shoot elongation and stem enlargement in potted rose plants through modulation of bioactive GA biosynthesis.